Socioeconomic and environmental effects of China's Conversion of Cropland to Forest Program after 15 years: a systematic review protocol - Gutiérrez Rodríguez, L.; Hogarth, N.J.; Zhou, W.; Putzel, L.; Xie Chen; Zhang, Kun. (Springer, 2015)
Agricultural activities on sloping lands have historically led to forest loss and degradation in China which, coupled with industrial pressures on the environment, were deemed responsible for catastrophic flooding events in the late 1990s. After these events, China’s forest policy underwent a significant reorientation towards ecological conservation and rural development, a process epitomized by the Conversion of Cropland to Forest Program (CCFP). Launched in 1999, the CCFP integrates both socioeconomic and environmental objectives with the aim of reforesting smallholder cropland on sloping lands, while compensating farmers with payments for their lost income. Following 15 years of implementation, it is timely to conduct a comprehensive assessment of the state of knowledge about the CCFP’s impacts on human populations and the environment.The primary research question asks “What socioeconomic and environmental effects has the Conversion of Cropland to Forest Program had on human populations and land resources during its first 15 years in China?” We use a theory of change and a Population-Intervention-Comparator-Outcome (PICO) framework to structure our systematic review, where populations of interest consist of both human populations and land resources targeted by the program, while the intervention of interest is the CCFP as defined by its component activities, including compensatory subsidies, skill-training, and enforcement with field checks. Outcomes are defined as both the socioeconomic and environmental impacts of the program. We will conduct a search for relevant English and Chinese language literature on Scopus, Web of Science, CAB Abstracts, AGRIS (FAO), and the China National Knowledge Infrastructure. Search results will be screened for relevance in a two stage process (titles and abstracts, followed by full texts) based on predefined eligibility criteria, and then further assessed for potential sources of bias. Extraction of data from those studies that have passed full-text screening will follow a coding protocol based on the PICO framework, and quantitative and qualitative analyses of the extracted data will be conducted and synthesized. Finally, a narrative report will present the findings of the review, alongside a geographic map illustrating the coverage of included studies compared with the actual implementation area of the CCFP.